PENERAPAN MODEL PROBLEM BASED LEARNING DALAM ASPEK PENALARAN BERFIKIR KRITIS SISWA - Salsa Oka Sabrina; Uyun Mulziyah; Fitriyani; Muhammad Nofan Zulfahmi (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study examines the application of problem-based learning (PBL) models in order to improve students' reasoning and critical thinking. Teachers are required to continue to develop themselves, especially in the learning process. This study uses a literature and qualitative approach to understand students' critical thinking analysis in completing learning using PBL. Critical thinking involves the ability to see an issue from multiple perspectives without prejudice. PBL requires u students.